Indicator taxa of spider (Araneae) diversity and their efficiency in conservation - Cardoso, Pedro; Silva, Israel; de Oliveira, Nuno G.; Serrano, Artur R. M. (Biological Conservation, 2004)
A considerable number of alternative approaches have been suggested during the last years to predict species richness of a given taxon, while retaining information on the identities of the observed individuals. Such information can be extremely useful for choosing conservation priority areas, either by using raw richness values or, preferentially, by considering the complementarity between potential sites. Among the most popular approaches is the use of indicator taxa. Both one single family and a group of several families are here tested in their ability to predict the number of spider (Araneae) species independently of sampling eﬀort, geographical location and type of habitat. We use data from three Portuguese protected areas as a test case. A two-family indicator group – Gnaphosidae and Theridiidae – is found to be a good surrogate of species richness, even if caution is needed regarding the comparison of sites with considerably diﬀerent sampling eﬀort or vegetation cover. No single family can be seen as a good surrogate of the totality of spiders. In addition, only a group of the two mentioned families is found to be eﬃcient and reliable either when used to rank sites according to taxa richness or for determining near-minimum sets of sites for conservation. We therefore recommend surrogacy with this indicator group as a promising approach for the prediction of spider species richness or evaluation and ranking of areas according to their conservation importance. The reached conclusions should uphold for Portugal and the entire Mediterranean region.
Keywords: Complementarity; estimation; Mediterranean; Portugal; Species richness

Indicator taxa of spider (Araneae) diversity and their efficiency in conservation - Cardoso, Pedro; Silva, Israel; de Oliveira, Nuno G; Serrano, Artur R M (Biological Conservation, 2004)
A considerable number of alternative approaches have been suggested during the last years to predict species richness of a given taxon, while retaining information on the identities of the observed individuals. Such information can be extremely useful for choosing conservation priority areas, either by using raw richness values or, preferentially, by considering the complementarity between potential sites. Among the most popular approaches is the use of indicator taxa. Both one single family and a group of several families are here tested in their ability to predict the number of spider (Araneae) species independently of sampling eﬀort, geographical location and type of habitat. We use data from three Portuguese protected areas as a test case. A two-family indicator group – Gnaphosidae and Theridiidae – is found to be a good surrogate of species richness, even if caution is needed regarding the comparison of sites with considerably diﬀerent sampling eﬀort or vegetation cover. No single family can be seen as a good surrogate of the totality of spiders. In addition, only a group of the two mentioned families is found to be eﬃcient and reliable either when used to rank sites according to taxa richness or for determining near-minimum sets of sites for conservation. We therefore recommend surrogacy with this indicator group as a promising approach for the prediction of spider species richness or evaluation and ranking of areas according to their conservation importance. The reached conclusions should uphold for Portugal and the entire Mediterranean region.
Keywords: Complementarity; estimation; Mediterranean; Portugal; Species richness

Indicator taxa of spider (Araneae) diversity and their efficiency in conservation - Cardoso, Pedro; Silva, Israel; de Oliveira, Nuno G; Serrano, Artur R M (Biological Conservation, 2004)
A considerable number of alternative approaches have been suggested during the last years to predict species richness of a given taxon, while retaining information on the identities of the observed individuals. Such information can be extremely useful for choosing conservation priority areas, either by using raw richness values or, preferentially, by considering the complementarity between potential sites. Among the most popular approaches is the use of indicator taxa. Both one single family and a group of several families are here tested in their ability to predict the number of spider (Araneae) species independently of sampling eﬀort, geographical location and type of habitat. We use data from three Portuguese protected areas as a test case. A two-family indicator group – Gnaphosidae and Theridiidae – is found to be a good surrogate of species richness, even if caution is needed regarding the comparison of sites with considerably diﬀerent sampling eﬀort or vegetation cover. No single family can be seen as a good surrogate of the totality of spiders. In addition, only a group of the two mentioned families is found to be eﬃcient and reliable either when used to rank sites according to taxa richness or for determining near-minimum sets of sites for conservation. We therefore recommend surrogacy with this indicator group as a promising approach for the prediction of spider species richness or evaluation and ranking of areas according to their conservation importance. The reached conclusions should uphold for Portugal and the entire Mediterranean region.
Keywords: Complementarity; estimation; Mediterranean; Portugal; Species richness